2015
DOI: 10.1177/1687814015613253
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental investigations of shape and location of vortex generators on fluid flow and heat transfer in a constant heat-fluxed rectangular duct

Abstract: A numerical and experimental study was conducted for heat transfer enhancement and fluid flow in a constant heatfluxed rectangular wooden duct fitted with two shapes of vortex generators (circular and square). These vortex generators are of the same area and placed at two different locations (X d = 1 cm and X d = 2 cm) ahead of the heater set and for Reynolds number from 32,000 to 83,000. The numerical and experimental results show an enhancement of heat transfer with the presence of vortex generators. This en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Their results depicted that among different models, the simple rectangular vortex generator, has a higher effect on heat transfer enhancement. The effect of shape and location of vortex generators (circular and square) on fluid flow and heat transfer in a constant heat-fluxed rectangular duct were investigated by Al-khishali and Ebaid (2015). Their results showed that the heat transfer enhancement using circular type is higher than the square type.…”
Section: Introductionmentioning
confidence: 99%
“…Their results depicted that among different models, the simple rectangular vortex generator, has a higher effect on heat transfer enhancement. The effect of shape and location of vortex generators (circular and square) on fluid flow and heat transfer in a constant heat-fluxed rectangular duct were investigated by Al-khishali and Ebaid (2015). Their results showed that the heat transfer enhancement using circular type is higher than the square type.…”
Section: Introductionmentioning
confidence: 99%